Candidate Genes In the Gut and Pancreas of Diabetes-prone Rats - Noel, Janet Ariana (Université d'Ottawa / University of Ottawa, 2013)
Type 1 diabetes (T1D) is an autoimmune disorder, targeting the β-cells of the pancreas. Processes occurring in the gut and pancreas are inferred to be involved. The pre-diabetic expression signature in these tissues is largely uncharacterized. HYPOTHESIS: Spontaneous models of T1D, the LEW.1AR1/Ztm-iddm rat (LEW-DP) and BioBreeding diabetes-prone rat (BBdp) exhibit a distinct transcriptional signature prior to T1D onset. Transcriptional profiling was used to elucidate the expression signatures of the LEW-DP gut and BBdp pancreas. The LEW-DP gut displayed decreased expression of markers of anti-inflammatory M2 macrophages. The LEW-DP rats showed an upregulation of markers of pro-inflammatory signaling when fed a diabetes-promoting cereal diet compared with LEW-DP rats fed a protective hydrolyzed casein diet. Prospective pancreatectomy was used to analyze T1D development in the BBdp rat. Significant upregulation of β-cell markers Reg3α, Reg3β, and Trim26 was observed in pre-diabetic rats. Thus, it was shown that environment modifies the transcriptional program and the transcriptional profile is programmed early to affect T1D development.
Keywords: Type 1 Diabetes; Gene Expression; Beta-cell; Diet; Pancreas; Jejunum